2017
DOI: 10.3389/fams.2017.00006
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Algorithms for Computational Systems Biology

Abstract: Computational systems biology aims at integrating biology and computational methods to gain a better understating of biological phenomena. It often requires the assistance of global optimization to adequately tune its tools. This review presents three powerful methodologies for global optimization that fit the requirements of most of the computational systems biology applications, such as model tuning and biomarker identification. We include the multi-start approach for least squares methods, mostly applied fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 83 publications
0
25
0
Order By: Relevance
“…The RCGAs provided in libRCGA can also handle constrained optimization problems. Constrained optimization formulations are suited to incorporate prior knowledge in the parameter estimation problems [2], [14], [16], [18]. It has been demonstrated that the stochastic ranking is very efficient in constrained optimization problems [22], [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The RCGAs provided in libRCGA can also handle constrained optimization problems. Constrained optimization formulations are suited to incorporate prior knowledge in the parameter estimation problems [2], [14], [16], [18]. It has been demonstrated that the stochastic ranking is very efficient in constrained optimization problems [22], [23].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic algorithms (GAs) are metaheuristic techniques developed with inspiration from the evolution of living organisms [13], [14]. The basic procedure is shown below.…”
Section: Genetic Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a consequence of the presence of nonlinear dynamics and path constraints. As a result, local optimization methods will usually converge to bad local solutions [45,145]. Often, researchers resort to the use of a multi-start strategy, i.e.…”
Section: Challenges and Pitfalls In Numerical Optimal Controlmentioning
confidence: 99%